Mitigating N2O emissions from clover residues by 3, 4-dimethylpyrazole phosphate (DMPP) without adverse effects on the earthworm Lumbricus terrestris. (January 2017) - Kong, Xianwang; Duan, Yunfeng; Schramm, Andreas; Eriksen, Jørgen; Holmstrup, Martin; Larsen, Thomas; Bol, Roland; Petersen, Søren O.
Abstract: In EU-28, temporary grasslands constitute more than 10% of the total arable land. Grassland tillage will return up to 400 kg N ha −1 in residues that can lead to a pulse of N2 O emissions. Here a novel application of the nitrification inhibitor 3, 4-dimethylpyrazole phosphate (DMPP) was evaluated in a 28-d mesocosm experiment, where DMPP spraying prior to tillage was simulated. Above-ground parts of 15 N-labelled clover residues were treated with DMPP and either placed at 10 cm depth to simulate ploughing (PL), or mixed with soil at 0–10 cm depth to simulate rotovation (RO). Earthworms ( Lumbricus terrestris ) were introduced to study their role in residue decomposition and N2 O emissions. Fluxes and isotopic composition of N2 O were determined with dynamic chambers using laser spectroscopy. A gradual increase in 15 N-enrichment of N2 O indicated that denitrification was the main source. DMPP reduced cumulative N2 O emissions in PL from 241 to 146 mg N m −2 ; the reduction in RO was smaller, from 103 to 94 mg N m −2, and not significant, possibly due to higher oxygen and soil NO3 − availability. After 28 d incubation, on average > 90% of the earthworms were recovered, and in vivo N2 O production from L. terrestris accounted for only 1–6% of residue-induced emissions. The guts were removed from worms to quantify DNA and m RNA of denitrifying genes ( nirK, nirS, nosZ clade I and II). It was found that earthworm in vivo N2 O production rates were negatively correlated to m RNA of nosZ-I, but positively to nir / nos ratio, suggesting the active involvement of denitrifiers associated with ingested feed in these emissions. Earthworm body tissue was enriched with 15 N, with no effect of DMPP. This showed that the worms had fed on the clover residues, and that DMPP did not interfere with feeding behavior or nitrogen assimilation. The observed effects show that DMPP treatment of clover residue before tillage has the potential to modify N2 O emissions without adverse effects on residue decomposition or soil fauna. Highlights: In a novel application, spraying of DMPP to grassland before ploughing or rotovation was simulated. 15 N-labelled clover residues traced origin of N2 O-N and earthworms ( L. terrestris) 15 N assimilation. DMPP reduced N2 O emissions induced by residues as modified by residue distribution. DMPP did not change L. terrestris feeding behavior, as shown by 15 N incorporation. Transcripts of denitrifying genes in earthworm guts were related to in vivo N2 O production.